Comparison of clinical and echocardiographic outcomes between mini-thoracotomy transatrial LuX-Valve transcatheter and surgical tricuspid valve replacement - Huang, Lei; Sun, Zhenxing; Cai, Yu; Xie, Yuji; Zhang, Ziming; Sun, Wei; Li, He; Fang, Lingyun; He, Lin; Zhang, Li; Yang, Yali; Wang, Jing; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background and aims Transcatheter tricuspid valve replacement (TTVR) has recently emerged as a novel therapeutic approach for managing severe tricuspid regurgitation (TR). However, surgical tricuspid valve replacement (STVR) continues to be the predominant treatment modality. There are limited comparative data on both procedures. This study aimed to compare clinical and echocardiographic outcomes between patients who underwent mini-thoracotomy transatrial LuX-Valve TTVR and those who underwent STVR. Methods This study prospectively collected patients with severe TR who underwent TTVR (n = 29) or isolated STVR (n = 59) at Wuhan Union Hospital from 2019 to 2022. All TTVR patients received the LuX-Valve via a mini-thoracotomy and transatrial approach. The clinical and echocardiographic outcomes were compared at 30-day and one-year follow-ups. Results At baseline, patients with LuX-Valve TTVR had higher surgical risk scores and a greater proportion of right ventricular dysfunction compared with STVR. In the early postoperative period, the STVR group had a greater decrease in right ventricular function. Hospital length of stay (LOS), intensive care unit LOS, total procedure time, and tracheal intubation time were shorter in the TTVR than in the STVR group. The incidence of postoperative paravalvular leaks was higher among patients who underwent TTVR. Compared to the STVR group, the pacemaker implantation rate was lower in the TTVR group. During follow-up, the peak tricuspid valve velocity and mean gradient in the TTVR group were consistently lower than those in the STVR group. There was similar mortality between TTVR and STVR at 30-day and one-year follow-ups. Conclusions The mini-thoracotomy transatria LuX-Valve TTVR has a higher incidence of paravalvular leaks and a lower rate of pacemaker implantation than STVR, with similar 30-day and one-year mortality rates. In some respects, mini-thoracotomy transatrial LuX-Valve TTVR may be a feasible and safe treatment option for specific populations, or it could potentially serve as an alternative therapy to supplement conventional STVR. Further follow-up is required to assess differences in long-term clinical outcomes and valve durability.